DESAIN KELOMPOK KERJA DAN IMPLEMENTASI EVALUASI BERKELANJUTAN DALAM PENINGKATAN MUTU PENDIDIKAN - Cut Rini Rahayu; Agus Salim Salabi (STKIP Pesisir Selatan, 2025)
Improving the quality of education requires a systematic approach through stakeholder collaboration and continuous data-based evaluation. This study analyzes the design of working groups and the implementation of continuous evaluation in improving the quality of education at SMP Ummul Ayman Samalanga. The research method uses a qualitative case study approach with in-depth interviews, participatory observation, and documentation studies. The results show that the working group design was developed through the strengthening of KKG and MGMP as collaborative forums for planning, reflection, and problem solving in learning. This collaboration encourages the more consistent application of active and project-based learning. Continuous evaluation using the PDCA cycle and CIPP model enabled the school to accurately identify learning issues and formulate follow-up measures through remedial-enrichment programs and the strengthening of a culture of literacy. The integration of collaborative working groups and data-based evaluation proved effective in reducing disparities in achievement between classes and creating sustainable improvements in education quality. The findings offer a practical model for other schools in systematic and measurable education quality improvement.